Gradient of Magnetic Field in Pulsar Star - Sandok, Mohamed; ALmohamedy, Abdul alrahman; ALbakri, Sundus (Iraqi Journal of Science, 2025)
The magnetic field of puisar (B), is considered to be magnetic dipole field. The pulsar is a neutron star The pulsar magnetic field is about (10% T), with high curvature and radius of (10’m). The work is interested on the geometry of the magnetic field within the light cylinder (R-3×10m). The model of pulsar, which we adopted, is that of Goldriech & Julian), the dipole axis is in the same axis of the star rotation it is an algned rotator. Within this consideration we studied the types of gradient with changing position angie (A) The first type, B-Gradient in tr) direction (VB), and the second type,-B-Gradient in (3) direction (VAB) The results indicated that the assumed magnetic field cunfiguration enable us to estimate, why the two types of Grad-B. Increase towards the infits of the Eight cylinder. Therefore we noted the magnetic field inside the light cylinder is very strong with high curvature for sar surisee Also, we concluded, after the boundary of (RL), the meggiatic fiead lines are open and the charges will be accelerate with high velecity and flow out the light cylinder.